A proposed rain attenuation prediction method for free space optical link based on rain rate statistics - Basahel, Ahmed; Islam, Md Rafiqul; Habaebi, Mohamed Hadi; Suriza, A Z (Asian Research Publishing Network (ARPN), 2015)
Free Space Optics technology has gained acceptance in telecommunication industry mostly in enterprise campus network. However in tropical regions, rainfall is the dominant factor that degrades the FSO link performance and its availability. In this paper, a method is proposed to estimate the total path attenuation due to rain for Free Space Optical communication links for all percentage of availabilities and any path length. Path length reduction factor for FSO has been derived using reduction factors models developed for microwave under measurement in tropical climate. Regression analysis has been applied and model is derived using best fit curve. Comparison between derived and measured reduction factors has been made for validation. Derived reduction factor seems to have strong agreement with both models which were derived based on measurements. This method can provide estimation of total path rain attenuation for FSO for all percentage of time with any path lengths.